Extrapolation-Based Scale Effect Model for Granular Heap Modulus - Zhigang Ma; Shuaifeng Wu; Ran Wei (Advances in Civil Engineering)
The numerical analysis was used to predict the rockfill dam displacement, and the model parameters were calibrated using the triaxial experiments on scale-down rockfill samples. Due to the scale effect of rockfill material, the displacements were usually underestimated in the design phase. This study focused on the scale effect of rockfill material and an extrapolation model was proposed to extrapolate the prototype modulus from the laboratory modulus. By conducting confined compression experiments, the size effect was investigated using ball heaps. Based on the experimental findings, considering a granular heap as a cumulative particle structure, the structural mechanics approach was introduced to establish the size effect model. Then, the boundary constrain effect model was speculated using the elastic mechanics analysis. By conducting the confined experiments on ball heaps, the modulus variation with particle breakage was investigated and the breakage effect model was established consequently. Finally, via combining the effects from the size, boundary constrain, and particle breakage, a scale effect model was established for extrapolating prototype modulus from the laboratory modulus. The proposed model was evaluated through numerical analysis of an actual dam. The experimental results revealed that the compressive modulus decreased as the initial void ratio increased; under the same initial void ratio, the compressive modulus decreased as the ratio of the specimen width to particle size increased; the compressive modulus decreased as the particle breakage increased. The numerical analysis results showed that prediction accuracy for rockfill dam displacement was improved by 8%–10%. The proposed model represents a new approach for investigating the scale effect of rockfill material, which could be adopted by engineers to improve the prediction of rockfill dam displacement.